Results of endovascular aneurysm repair of infrarenal aorta and iliac arteries in patients with severe concomitant diseases - P. A. Galkin; A. V. Svetliko (Вестник хирургии имени И.И. Грекова)
The objective of this study was to assess the efficacy and safety of endovascular aneurysm repair (EVAR) of infrarenal aorta (IA) and iliac arteries (IA) with favorable and unfavorable anatomy in the group of high-risk patients after surgery and at follow-up examinations.Material and methods. The study is based on the results of the study of 95 patients with abdominal aortic aneurysms and iliac arteries aneurysms who underwent EVAR at Healthcare «Clinical Hospital № 122 named after L.G. Sokolov» for the period from March 2008 to December 2016. RESULTS. Results of EVAR of infrarenal aorta and iliac arteries in patients with severe concomitant diseases were analyzed. The interventions were successful in 100 % of cases.Сonclusions. The study has shown that EVAR is an effective and safe method of treatment for endovascular aneurysm repair of infrarenal aorta and iliac arteries in high-risk patients. Long-term care requires abdominal aorta and iliac artery examination with the use of duplex ultrasound angioscanning and multispiral computed tomoangiography to identify specific complications.